2021
DOI: 10.34172/joddd.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microcrack formation during root canal preparation using hand, rotary files and self-adjusting file in primary teeth: An in vitro study

Abstract: Background. Pediatric endodontics is a field with constant evolution, resulting in the shifting of paradigms from the use of conventional hand files to rotary files for biomechanical preparation in primary teeth. Biomechanical preparation plays a crucial role in the success of root canal treatment. Primary teeth need special attention since they differ from permanent teeth in root canal morphology. Cleaning and shaping of the canals damage the root dentin, leading to dentinal cracks. Newer techniques for root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Excessive removal of the radicular dentin, especially in "danger zones," may result in strip perforation and vertical root fractures. In addition, the gradual dentinal sclerosis caused by the age-related change in the microstructure of dentin may be correlated with decreased resistance to damage initiation and propagation [ 3 , 10 ]. As the thickness of the dentinal wall directly relates to the tooth's resistance to lateral stresses, excessive canal preparation compromises dentinal thickness and weakens the tooth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive removal of the radicular dentin, especially in "danger zones," may result in strip perforation and vertical root fractures. In addition, the gradual dentinal sclerosis caused by the age-related change in the microstructure of dentin may be correlated with decreased resistance to damage initiation and propagation [ 3 , 10 ]. As the thickness of the dentinal wall directly relates to the tooth's resistance to lateral stresses, excessive canal preparation compromises dentinal thickness and weakens the tooth.…”
Section: Discussionmentioning
confidence: 99%
“…In endodontic therapy, the prognosis is positively connected with the most effective cleaning and shaping techniques [ 1 ]. Nickel-titanium (NiTi) rotary instruments have significantly improved root canal preparation since they have made instrumentation easier and faster [ 2 , 3 ]. Human dentin is viscoelastic, and during biomechanical preparation, instruments contact the root canal wall and apply forces that lead to a temporary stress concentration on the dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that molars prepared by H-files had higher fracture root resistance (mean ±SD 729.38±110.07) than molars prepared by Fanta AF baby files (±SD 668.19±120.62), but without significant difference (P=0.189). This could be explained by the fact that rotary files cause more microcracks or craze lines on the dentinal walls during preparation (Panda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Microcracks or craze lines sometimes appear on the walls because of the rotational force used to prepare root canals with rotary files. The instruments' flute shape, crosssectional geometry, tip design, progressive or continuous taper, constant or variable pitch, and other factors all contribute to the severity of these defects (Panda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%